The mechanism of slope instability due to rainfall-induced structural decay of earthquake-damaged loess - Hu Tao; Mengmeng Zhang; Li Gong; Xi Shi; Yijie Wang; Guoqiang Yang; Shaowei Lei (Earthquake Research Advances, 2022)
Natural loess slopes are characterized by a strong geological structure, which is an important factor in maintaining slope stability. The magnitude and duration of the earthquake may disturb the soil structure at different levels degrees, locally changing the arrangement between soil particles. The process of rainfall humidification weakens the cementation between soil particles, and the disturbance and humidification change the structural state of the soil, which in turn causes sliding of the slope along with the decay of soil mechanical properties. As slope instability is often the result of a series of post-earthquake ripple effects, it is of great scientific significance to study the mechanism of slope instability due to the structural decay of earthquake-damaged loess exacerbated by rainfall. In this paper, the impact of structural decay of loess on slope stability is simulated by GEOSTUDIO software under three conditions: pre-earthquake rainfall, post-earthquake rainfall and earthquake, taking the landslide in Buzi Village, Min County, Gansu Province as an example. The comparative analysis of the calculation results shows that the structural properties of the slope without earthquake disturbance are influenced by infiltration amount. When it is fully saturated, the structural properties are similar to those of saturated soil, and the safety factor is reduced by 12.9%. In addition, the earthquake intensity and duration have different degrees of structural damage to the soil. When the structure is fully damaged, it is similar to that of remodelled soil, and the safety factor is reduced by 45.84%. Notably, the process of the earthquake and the following humidification generates the most serious damage to the loess structure, with a reduction in the safety factor of up to 56.15%. The quantitative analysis above obviously illustrates that the post-earthquake rainfall causes the most severe damage to structural loess slopes, and the resulting landslide hazard should not be underestimated.